Penilaian E-Service Melalui Respon Pengguna Aplikasi Tangerang Live Terhadap Kepuasan Masyarakat Kota Tangerang Menggunakan SPSS Versi 26 - Asmoro, Songsong; Aditya, Toddy; Ginanjar, Arief; Setiawan, Slamet (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2024)
Technological developments in the era of digitalization have brought major changes to the needs of the community, especially in Tangerang City, including electronic-based community services (E-Service), which continue to increase. Therefore, the Tangerang City government created an application called Tangerang Live to help the government respond to suggestions and input from the public. In this research, the author applies quantitative research methods by randomly collecting samples from the total population of Tangerang Live application users of 546,111 users in 2021, then carrying out calculations using the Slovin formula to get the number of samples used in this research to be 400 users. Data collection in this research uses the relationship between the E-Service and community satisfaction variables. This research aims to prove the influence that occurs between these two variables. The 28 questionnaire statements were declared valid and reliable because the calculated r value and reliability value were greater than the table r value. The hypothesis in this research is proven that there is a positive and significant relationship between E-Service and community satisfaction. The conclusion of this research states that the better the quality of E-Service in the Tangerang Live application, the more substantial jurisdiction it will have on the level of satisfaction of the people who use the Tangerang Live application.